Effectiveness of Geogrids on Rutting and Bearing Capacity of Sub-base Course - Mardookhpour, Ali Reza (Nepal Journal of Science and Technology, 2015)
Geogrids are being used in transportation application often in embankment construction due to their ease of construction and economy compared to traditional methods. Utilizing polymer materials in order to improve the performance of road structure is based on two factors, decreasing deformation and increasing bearing capacity. In this study geogrids were tested to check the ability of increasing load carrying capacity for highway projects. The purpose of this research work was to find a relation between the loading of the geogrid, the thickness of the aggregate layer and its bearing capacity. This would normally lead to an investigation on the lateral restrain behavior of a geogrid. According to the results obtained from soil mechanics laboratory, it could be demonstrated that by utilizing geogrids , the probability of occurring rutting decreases 30% and the bearing capacity of soil increase 40 % respectively. DOI: http://dx.doi.org/10.3126/njst.v15i1.12020 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 77-80